Avaliação de impactos ambientais da construção: comparação entre sistemas construtivos em alvenaria e em wood light frame - Santos, Larissa Carrera Fernandes dos (2012)
The study shows an assessment of environmental impacts of two construction systems, masonry and Wood Light Frame. To base it, it was used the principles of Life Cycle Analysis and Environmental Impact Studies. The scope adaptation of the environmental impact assessment was the contribution of the principles of Life Cycle Analysis, as well as the evaluation in steps of the building cycle. In the study it was found that the buildings in Wood Light Frame are better to environmental conservation in various aspects then the construction system in masonry. That is because the first has less impacts along the life cycle of buildings. The results showed also arguments to the consumer and professionals in the construction industry about which are the most significant environmental impacts so to consider them when deciding the type of construction.